Job Stress and Its Effects on Job Performance of Employees: Ghana Revenue Authority in Tamale Metropolis as a Case Study - Issahaku , Adams; Ruhana, Sein Alhassan (Journal of Social Science Studies, 2023)
Competition among businesses in today’s ever-dynamic environment places a high demand and burden on employees. These demands induce stress on employees with the consequences of individual health challenges, family breakdown, pressure on social amenities, low productivity and profitability of firms. This study was undertaken to establish the implications of job-related stress on employees’ job performance. The sample comprises all workers of Ghana Revenue Authority (GRA) in Tamale, the Northern Region of Ghana. All employees (census) were used for the study and data was collected using both primary and secondary sources. The findings revealed that stress is a normal occurrence at the workplace that affects all people, regardless of their gender or socioeconomic class, hence, the need for management to formulate a good policy directed at reducing stress among workers, and encouraging high performance among workers. This will help reduce job-related stress. Managers must be dedicated to making adjustments that will assist workers to cope with some of the known stressors. It is recommended that managers should match individual capabilities with the tasks and duties allocated to avoid both physical, emotional and psychological pressure on the employee. Management should establish a congenial and collegial atmosphere for working and operate an open-door communication policy as a management style because this will ease pressure and tension since leadership style was cited as a stressor.